Zwei "Ziegelwracks" in der Kieler Aussenförde? Der Fund der MALIK und des 2-Anker Wracks - Grassel, Philipp (Arkæologi i Slesvig-Archäologie in Schleswig, 2021)
In 2015 and 2016, two unknown wrecks – the MALIK and the 2-Anker Wrack – were found in the Kiel Fjord. Both sites were investigated by short surveys during 2015, 2016, and 2018. The large amount of bricks covering the wrecks is characteristic of both sites. This article gives an overview of past and current research on the wrecks. Additionally, an initial interpretation of the context of the wrecks is suggested including a possible research project. From the author's point of view, both wrecks were once most likely small wooden sailing ships for commercial purposes; such vessels were very common on the coasts of the Baltic Sea and the North Sea. Due to the lack of usable archaeological data, a detailed dating of the wrecks is not yet possible. Comparative analyses of the anchors and the visible, structural parts of the wrecks roughly date wrecks to the period between the 1830s and the first half of the 20th century.